Internal shortest absent word queries in constant time and linear space - Badkobeh, Golnaz; Charalampopoulos, Panagiotis; Kosolobov, Dmitry; Pissis, Solon P. (Theoretical computer science, 2022)
Given a string T of length n over an alphabet Σ⊂{1,2,…,nO(1)} of size σ, we are to preprocess T so that given a range [i,j], we can return a representation of a shortest string over Σ that is absent in the fragment T[i]⋯T[j] of T. We present an O(n)-space data structure that answers such queries in constant time and can be constructed in O(nlogσ⁡n) time.